Novel branched poly (aryl piperidinium) copolymer ionomer, anion exchange membrane and preparation method thereof

Chemical stability of anion exchange membrane in alkaline fuel cells is solved by introducing branched piperidinium groups without aryl ether bonds into the polymer backbone. The chemical stability of anion exchange membrane in alkaline fuel cells is solved. and the problem of insufficient mechanical properties, stable operation and excellent water management capabilities under low humidity conditions, and are suitable for a variety of batteries and electrolytic devices.

CN119234011APending Publication Date: 2024-12-31INDUSTRY UNIVERSITY COOPERATION FOUNDATION HANYANG UNIVERSITY

Patent Information

Application Number
CN202380041854.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-04
Filing Date
2023-06-01
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing anion exchange membranes have problems in alkaline fuel cells with poor chemical stability, insufficient mechanical properties, limited chemical stability and low power density, and are insufficient durability and water management capabilities when used under low humidity conditions.

Method used

Develop a branched poly(aryl piperidinium) copolymer ionomer to prepare excellent chemical stability by introducing branched piperidinium groups into the polymer backbone without aryl ether bonds, Anion exchange membrane with high molecular weight, mechanical properties and low swelling rate is suitable for alkaline fuel cells and water electrolytic devices.

Benefits of technology

The anion exchange membrane can operate stably under low humidity conditions, has excellent water management capabilities and high ionic conductivity, improves the durability and performance of fuel cells, and is suitable for alkaline fuel cells, water electrolytic devices, carbon dioxide reduction, vanadium Redox flow batteries and metal-air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234011A_ABST
    Figure CN119234011A_ABST
Patent Text Reader

Abstract

The present invention relates to a poly (arylpiperidinium) copolymer ionomer which does not have an aryl ester bond in a polymer backbone and has a branched piperidinium group introduced into a repeating unit, thereby having excellent chemical stability, excellent mechanical properties, and excellent mechanical properties. And meanwhile, the polymer has the advantages of high molecular weight, low swelling ratio, high dimensional stability, high ionic conductivity and limited phenyl adsorption effect. Furthermore, the anion exchange membrane prepared from the branched poly (arylpiperidinium) copolymer ionomer can be operated under low humidity conditions and is excellent in water management, and thus can be applied to membranes and binders for alkaline fuel cells, water electrolysis devices, carbon dioxide reduction, vanadium redox flow batteries, or metal-air batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a novel branched poly(arylpiperidinium) copolymer ionomer, anion exchange membrane and a preparation method thereof, and more specifically, to a technology for synthesizing a poly(arylpiperidinium) copolymer ionomer, wherein the poly(arylpiperidinium) copolymer ionomer has no aryl ether bond in the polymer backbone and has a branched piperidinium group introduced into a repeating unit, and an anion exchange membrane is prepared from the poly(arylpiperidinium) copolymer ionomer and applied to an alkaline fuel cell and a water electrolysis device. Background Art

[0002] To date, many studies have been conducted on polymer electrolyte membrane fuel cells (PEMFCs) due to their relatively high current density and environmental friendliness. Perfluorocarbon-based proton exchange membranes represented by Nafion are mainly used as polymer electrolyte membranes. However, since the use of platinum-based noble metal catalysts is necessary for Nafion membranes due to their low oxygen reduction reaction (ORR) activity, research is being actively conducted, including the development of aromatic-based polymer electrolyte membranes, etc., to replace Nafion, which is very expensive and has a low glass transition temperature.

[0003] In this regard, research on alkaline membrane fuel cells (AMFCs) and water electrolysis using anion exchange membranes is ongoing, as it is known that excellent performance and extremely high price competitiveness can be achieved even when inexpensive non-precious metals (such as nickel, manganese, etc.) are used as electrode catalysts instead of platinum. However, due to the problem of poor long-term stability caused by the decomposition behavior of hydroxyl radicals and ions during operation, research is needed to improve the durability of alkaline membrane fuel cells.

[0004] As an anion exchange membrane for alkaline membrane fuel cells, a synthesis method of introducing benzyltrimethylammonium groups into aromatic polymers based on aryl ethers (such as polysulfone (PSF), polyphenyl ether (PPO) or polyether ether ketone (PEEK)) is known. The advantage of this method is that the solubility of the polymer is improved as repeating units with aryl ether (CO) bonds are formed along the polymer backbone. However, because the aryl ether bonds in the polymer backbone reduce the long-term stability due to the hydroxyl radical degradation behavior of the electrolyte membrane during operation, it is necessary to improve the durability of the alkaline membrane fuel cell by preventing the decomposition of the polymer backbone.

[0005] In addition, because common anion exchange membranes have limited chemical stability (less than 500 h in 1 M NaOH solution at 80 °C) and mechanical properties (tensile strength less than 30 MPa), fuel cells using them have low power density (0.1 W cm -2 -0.5W·cm -2 ) and low durability. In addition, due to the high adsorption effect of the phenyl structure, there is a problem that the formation of a three-phase interface is limited, and when it is used as a binder, the fuel efficiency is reduced.

[0006] In addition, the moisture permeability of anion exchange polymers is very important for water management in anion exchange membrane fuel cells. Although water may overflow at the anode due to electrochemical water generation, the cathode tends to dry out due to water consumption. Therefore, polymers with high water content and swelling rate greatly affect durability because mass transfer resistance increases and electrochemical stability is hindered.

[0007] A poly(arylpiperidinium) copolymer ionomer having no aryl ether bond in the polymer backbone and having a branched piperidinium group introduced into a repeating unit has not been synthesized, and a technique for applying the poly(arylpiperidinium) copolymer ionomer to an alkaline fuel cell membrane and adhesive or water electrolysis is not clearly known.

[0008] Therefore, the inventors of the present disclosure have been continuously researching to broaden the application range of aromatic polymer ion exchange membranes with excellent thermal stability, chemical stability and mechanical properties. They attempt to solve the problems of conventional anion exchange polymers, such as low molecular weight, ionic conductivity, water content, mechanical properties, power density, durability, etc., by introducing a branched portion containing a piperidinium group in the repeating unit of the anion exchange polymer. Anion exchange membranes are prepared by synthesizing poly (aryl piperidinium) copolymer ionomers (in which a piperidinium group containing a branched portion is introduced into the polymer backbone without an aryl ether bond), and it is found that it can be applied to alkaline fuel cell membranes and adhesives of water electrolysis devices, carbon dioxide reduction, vanadium redox flow batteries, metal-air batteries, etc., thereby completing the present disclosure.

[0009] [References of related technologies]

[0010] [Patent document]

[0011] Patent Document 1: Korean Patent Publication No. 10-2018-0121961

[0012] Patent Document 2: International Patent Publication No. WO 2019 / 068051

[0013] Patent Document 3: Japanese Patent Publication No. JP 2020-536165

[0014] Patent Document 4: U.S. Patent Publication No. US2019 / 0036143 Summary of the invention

[0015] Technical issues

[0016] The present disclosure is developed in view of the above problems. The present disclosure is directed to providing a novel branched poly(arylpiperidinium) copolymer ionomer and a preparation method thereof, the ionomer having excellent chemical stability, high molecular weight, excellent mechanical properties, low swelling ratio, high dimensional stability and ionic conductivity, and limited phenyl adsorption effect.

[0017] The present disclosure also relates to the preparation of anion exchange membranes from branched poly(arylpiperidinium) copolymer ionomers, so that they can be applied to alkaline fuel cell membranes and adhesives, which can operate even under low humidity conditions and have excellent water management capabilities for water electrolysis devices, carbon dioxide reduction, vanadium redox flow batteries, metal-air batteries, etc.

[0018] Technical Solution

[0019] The present disclosure provides a branched poly(arylpiperidinium) copolymer ionomer having a repeating unit represented by [Chemical Formula 1].

[0020] [Chemical formula 1]

[0021]

[0022] In Chemical Formula 1, the aromatic monomer is selected from one or more compounds represented by the following structural formulas:

[0023]

[0024] Furthermore, the branching agent is selected from any one of the compounds represented by the following structural formulas:

[0025]

[0026] In addition, the present disclosure provides a method for preparing a branched poly(arylpiperidinium) copolymer ionomer, comprising:

[0027] (I) a step of dissolving the following substances as monomers in an organic solvent to form a solution: (a) one or more compounds selected from the group consisting of the following structural formulae,

[0028]

[0029] (b) one or more compounds selected from the group consisting of the following structural formulae,

[0030]

[0031] and (c) 1-methyl-4-piperidinone;

[0032] (II) a step of obtaining a viscous solution by gradually adding a strong acid catalyst to the solution and stirring the mixture;

[0033] (III) a step of obtaining a solid polymer by precipitating, washing and drying the viscous solution;

[0034] (IV) a step of adding K2CO3 and an excess of methyl halide to a polymer solution and reacting them to form a quaternary piperidinium salt, wherein the polymer solution is obtained by dissolving the solid polymer in an organic solvent; and

[0035] (V) The steps of precipitating, washing and drying the polymer solution.

[0036] Additionally, the present disclosure provides an anion exchange membrane comprising a branched poly(arylpiperidinium) copolymer ionomer.

[0037] In addition, the present disclosure provides a method for preparing an anion exchange membrane, which includes: (i) a step of dissolving a branched poly(arylpiperidinium) copolymer ionomer in an organic solvent to form a polymer solution; (ii) a step of casting the polymer solution on a glass plate and drying to obtain a membrane; and (iii) a step of treating the obtained membrane with 1M NaHCO3 or 1M NaOH, washing the obtained membrane with ultrapure water for multiple times and drying.

[0038] Additionally, the present disclosure provides a binder for an alkaline fuel cell comprising a branched poly(arylpiperidinium) copolymer ionomer.

[0039] In addition, the present disclosure provides an alkaline fuel cell including the anion exchange membrane.

[0040] In addition, the present disclosure provides a water electrolysis device including the anion exchange membrane.

[0041] In addition, the present disclosure provides a carbon dioxide reduction device including the anion exchange membrane.

[0042] In addition, the present disclosure provides a vanadium redox flow battery including the anion exchange membrane.

[0043] In addition, the present disclosure provides a metal-air battery including the anion exchange membrane.

[0044] Beneficial Effects

[0045] The novel branched poly(arylpiperidinium) copolymer ionomers according to the present disclosure have excellent chemical stability, high molecular weight and excellent mechanical properties, low swelling ratio, high dimensional stability and ionic conductivity, and limited phenyl adsorption effect.

[0046] Furthermore, since the anion exchange membranes prepared from the branched poly(arylpiperidinium) copolymer ionomers can operate even under low humidity conditions and have excellent water management capabilities, they can be applied to alkaline fuel cell membranes and adhesives, water electrolysis devices, carbon dioxide reduction, vanadium redox flow batteries, metal-air batteries, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The NMR ( 1 H NMR) spectrum.

[0048] Figure 2 The NMR spectra of b-PDTM-Tbp-3.5 and b-PDTP-Tbp-3.5 prepared in Example 5 and b-PFBM-Tbp-3.5 and b-PFBP-Tbp-3.5 prepared in Example 7 are shown ( 1 H NMR) spectrum.

[0049] Figure 3 The anion exchange membrane (I - Mechanical properties of anion exchange membranes prepared in the following forms (prepared from the copolymer ionomers obtained in Examples 1-8) and Comparative Examples 1 and 2.

[0050] Figure 4 The anion exchange membrane (OH - The swelling ratio and water absorption ratio of the anion exchange membranes prepared in the form of copolymer ionomers obtained in Examples 1-8) and Comparative Examples 1 and 2.

[0051] Figure 5 The hydrogen permeability of the anion exchange membrane prepared in Example 9 (prepared from the copolymer ionomers obtained in Examples 1 to 8) and the anion exchange membrane prepared in Comparative Example 1 are shown.

[0052] Figure 6 The fuel cell performance of anion exchange membranes prepared in Example 9 with different anode and cathode binders b-PDTP-Trip-5 [Binder A / C b-PFBP-Trip-3.5 according to Example 3 and Binder A / C b-PFBP-Trip-5 according to Example 4] is shown.

[0053] Figure 7 The fuel cell performance of b-PDTP-Trip-3.5 and b-PDTP-Trip-5 is shown, where the anode and cathode binders of b-PFBP-Trip-5 according to Example 4 were applied to the anion exchange membrane prepared in Example 9.

[0054] Figure 8 The fuel cell performance of the anion exchange membrane prepared in Example 9 with different anode and cathode binders b-PDTP-Trip-3.5 [Binder A / C b-PFBP-Trip-3.5 according to Example 3 and Binder A / C b-PFBP-Trip-5 according to Example 4] under low humidity conditions is shown.

[0055] Fig. 9 The fuel cell performance of b-PDTP-Trip-3.5 and b-PDTP-Trip-5 is shown, where the anode and cathode binders of b-PFBP-Trip-3.5 according to Example 3 were applied to the anion exchange membrane prepared in Example 9.

[0056] Fig.10 The water electrolysis performance of b-PDTP-Trip-5 is shown, in which the anion exchange membrane prepared in Example 9 was used according to the contents of the anode and cathode ionomers.

[0057] Fig.11 The anion exchange membrane prepared in Example 9 showed a -2 and long-term stability at 60°C for 110 hours, where b-PDTP-Trip-5 (film thickness 50 μm) was used. DETAILED DESCRIPTION

[0058] Hereinafter, the novel branched poly(arylpiperidinium) copolymer ionomer, anion exchange membrane and preparation method thereof according to the present disclosure will be described in detail.

[0059] The present disclosure provides a branched poly(arylpiperidinium) copolymer ionomer having a repeating unit represented by [Chemical Formula 1].

[0060]

[0061] In Chemical Formula 1, the aromatic monomer is selected from one or more compounds represented by the following structural formulas:

[0062]

[0063] Furthermore, the branching agent is selected from any one of the compounds represented by the following structural formulas:

[0064]

[0065] As can be seen from Chemical Formula 1, the branched poly(arylpiperidinium) copolymer ionomer according to the present disclosure has improved mass transfer capacity of the alkaline fuel cell catalyst layer due to the increase in the free volume of the polymer including the branched portion. In addition, the high water retention capacity enables it to operate stably under low relative humidity conditions and reduces the adsorption force on the catalyst surface, which helps to improve the fuel cell performance due to the activation of the electrode and increase the stability of the entire system.

[0066] In addition, the branched poly(arylpiperidinium) copolymer ionomer is substantially free of aryl ether groups in the polymer backbone and has excellent chemical stability due to the presence of stable N-heterocyclic ammonium groups. In addition, it also has a high molecular weight and excellent durability and mechanical properties compared to linear polymers.

[0067] In addition, the present disclosure provides a method for preparing a branched poly(arylpiperidinium) copolymer ionomer, comprising:

[0068] (I) a step of dissolving the following substances as monomers in an organic solvent to form a solution: (a) one or more compounds selected from the group consisting of the following structural formulae,

[0069]

[0070] (b) one or more compounds selected from the group consisting of the following structural formulae,

[0071]

[0072] and (c) 1-methyl-4-piperidinone;

[0073] (II) a step of obtaining a viscous solution by gradually adding a strong acid catalyst to the solution and stirring the mixture;

[0074] (III) a step of obtaining a solid polymer by precipitating, washing and drying the viscous solution;

[0075] (IV) a step of adding K2CO3 and an excess of methyl halide to a polymer solution and reacting them to form a quaternary piperidinium salt, wherein the polymer solution is obtained by dissolving the solid polymer in an organic solvent; and

[0076] (V) The steps of precipitating, washing and drying the polymer solution.

[0077] The organic solvent in step (I) may be one or more halogen-based solvents selected from dichloromethane, chloroform, dichloroethane, dibromomethane and tetrachloroethane. Specifically, dichloromethane may be used.

[0078] And, the strong acid catalyst in step (II) can be trifluoroacetic acid, trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoro-1-propanesulfonic acid, perfluoropropionic acid, heptafluorobutyric acid or a mixture thereof. Specifically, a mixture of trifluoroacetic acid and trifluoromethanesulfonic acid can be used.

[0079] Furthermore, the organic solvent in step (IV) may be N-methylpyrrolidone, dimethylacetamide, dimethyl sulfoxide or dimethylformamide.

[0080] Furthermore, in step (IV), the polymer is reacted with a methyl halide to form a quaternary piperidinium salt. Fluoromethane, methyl chloride, methyl bromide or methyl iodide, particularly methyl iodide, can be used as the methyl halide.

[0081] Additionally, the present disclosure provides an anion exchange membrane comprising a branched poly(arylpiperidinium) copolymer ionomer.

[0082] The anion exchange membrane according to the present disclosure has excellent chemical stability, which is due to the structure of the copolymer ionomer having N-heteroammonium groups and no aryl ether bonds in the polymer backbone. In addition, due to the structure of the introduced branched portion, it not only has a high molecular weight, excellent dimensional stability and mechanical properties, but also has a unique effect of suppressing swelling rate, while having high ionic conductivity.

[0083] In addition, the present disclosure provides a method for preparing an anion exchange membrane, which includes: (i) a step of dissolving a branched poly(arylpiperidinium) copolymer ionomer in an organic solvent to form a polymer solution; (ii) a step of obtaining a membrane by casting the polymer solution on a glass plate and drying; and (iii) a step of treating the obtained membrane with 1M NaHCO3 or 1M NaOH, washing the obtained membrane with ultrapure water for multiple times and drying.

[0084] The organic solvent in step (i) may be N-methylpyrrolidone, dimethylacetamide, dimethyl sulfoxide or dimethylformamide.

[0085] And, the concentration of the polymer solution may be specifically 2wt% to 30wt%, more specifically 3.0wt% to 5.0wt%. If the concentration of the polymer solution is lower than 2wt%, the ability to form a film may be reduced. And, if it exceeds 30wt%, the physical properties of the film may deteriorate after preparation because the viscosity increases significantly.

[0086] And, specifically, the drying in step (ii) can be performed by gradually removing the organic solvent in an oven at 80 to 90° C. for 24 hours, and then completely removing the organic solvent by heating in a vacuum oven at 120 to 150° C. for 12 hours.

[0087] Subsequently, the halide form (I - The branched poly(arylpiperidinium) copolymer ionomer membrane (in the form of HCO 3- or OH - Anion exchange membrane in the form of.

[0088] Additionally, the present disclosure provides a binder for an alkaline fuel cell comprising a branched poly(arylpiperidinium) copolymer ionomer.

[0089] In addition, the present disclosure provides an alkaline fuel cell including the anion exchange membrane.

[0090] In addition, the present disclosure provides a water electrolysis device including the anion exchange membrane.

[0091] In addition, the present disclosure provides a carbon dioxide reduction device including the anion exchange membrane.

[0092] In addition, the present disclosure provides a vanadium redox flow battery including the anion exchange membrane.

[0093] In addition, the present disclosure provides a metal-air battery including the anion exchange membrane.

[0094] Hereinafter, embodiments and comparative examples according to the present disclosure will be explained in detail with reference to the accompanying drawings.

[0095] [Examples 1 and 2] Preparation of triptycene-branched poly(arylpiperidinium) copolymer ionomers

[0096] Diphenylethane [DP, 6.75mmol (1.23g)], p-terphenyl [TP, 20.25mmol (4.663g)], triptycene [1mmol (0.254g)] and 1-methyl-4-piperidone [MP, 34.2mmol (3.87g)] were added as monomers to a 100mL reactor. Then, the monomers were dissolved while adding dichloromethane (DCM, 24mL) under stirring to form a solution. After the solution was cooled to -1°C, a mixture of trifluoroacetic acid (TFA, 3.6mL) and trifluoromethanesulfonic acid (TFSA, 30mL) was slowly added to the solution. The mixture was stirred and reacted for 2 hours to obtain a viscous solution. The viscous solution was poured into distilled water for precipitation, washed with deionized water for multiple times, and dried in an oven at 80°C for 24 hours to prepare a solid phase triptycene branched poly(diphenyl-co-terphenyl N-methylpiperidine) copolymer (yield 92%), which was named b-PDTM-Trip-3.5.

[0097] Next, after obtaining a polymer solution by dissolving the prepared b-PDTM-Trip-3.5 (20 mmol) in dimethyl sulfoxide (200 mL), K2CO3 (6.9 g, 50 mmol) and iodomethane [MeI, 60 mmol (8.46 g)] were added to the polymer solution and reacted in a dark room at room temperature for 24 hours to form a quaternary piperidinium salt. Next, the polymer solution was precipitated in 500 mL of ethyl acetate, filtered, washed with deionized water for multiple times, and completely dried in a convection oven at 80° C. to prepare a solid phase of triptycene-branched poly (diphenyl-co-terphenyl N-methylpiperidine) copolymer ionomer (yield 83%), which was named b-PDTP-Trip-3.5. The synthetic route is shown in Scheme 1 (Example 1).

[0098]

[0099] Scheme 1. Synthetic route of triptycene-branched poly(diphenyl-co-terphenyl N,N-dimethylpiperidinium) copolymer ionomers

[0100] In addition, by adjusting the molar fraction X (%) of triptycene in Scheme 1 to 5%, a triptycene-branched poly(diphenyl-co-terphenyl N,N-dimethylpiperidinium) copolymer and its ionomer were prepared in the same manner as in Example 1, and they were named b-PDTM-Trip-5 and b-PDTP-Trip-5 (Example 2), respectively.

[0101] [Examples 3 and 4] Preparation of Triptylene Branched Poly(arylpiperidinium) Copolymer Ionomers

[0102] A triptycene-branched poly(fluorene-co-biphenyl N,N-dimethylpiperidinium) copolymer and its ionomer were prepared in the same manner as in Examples 1 and 2, except that 9,9'-dimethylfluorene and biphenyl were used instead of diphenylethane and p-terphenyl as monomers, and they were named b-PFBM-Trip-3.5 and b-PFBP-Trip-3.5 (Example 3) and b-PFBM-Trip-5 and b-PFBP-Trip-5 (Example 4), respectively. The synthetic route is shown in Scheme 2 (triptycene-branched poly(fluorene-co-terphenyl N,N-dimethylpiperidinium) copolymer and its ionomer were also prepared using p-terphenyl of Example 1 instead of biphenyl in Example 4, and they were named b-PFTM-Trip-5 and b-PFTP-Trip-5, respectively).

[0103]

[0104] Scheme 2. Synthetic route of poly(fluorene-co-biphenyl N,N-dimethylpiperidinium) copolymer ionomers containing triptycene branches

[0105] [Examples 5 and 6] Preparation of 1,3,5-Triphenylbenzene Branched Poly(arylpiperidinium) Copolymer Ionomers

[0106] Except that 1,3,5-triphenylbenzene was used instead of triptycene as the monomer, a poly(diphenyl-co-terphenyl N,N-dimethylpiperidinium) copolymer branched with 1,3,5-triphenylbenzene and its ionomer were prepared in the same manner as in Example 1, and they were named b-PDTM-Tpb-3.5 and b-PDTP-Tbp-3.5 (Example 5) and b-PDTM-Tbp-5 and b-PDTP-Tbp-5 (Example 6), respectively.

[0107] The synthetic route is shown in Scheme 3.

[0108]

[0109] Scheme 3. Synthetic route for poly(diphenyl-co-terphenyl N,N-dimethylpiperidinium) copolymer ionomers containing 1,3,5-triphenylbenzene branches

[0110] [Examples 7 and 8] Preparation of 1,3,5-Triphenylbenzene Branched Poly(arylpiperidinium) Copolymer Ionomers

[0111] Except that 1,3,5-triphenylbenzene was used instead of triptycene as the monomer, a poly(fluorene-co-biphenyl N,N-dimethylpiperidinium) copolymer and its ionomer containing 1,3,5-triphenylbenzene branching were prepared in the same manner as in Example 3, and they were named b-PFBM-Tpb-3.5 and b-PFBP-Tbp-3.5 (Example 7) and b-PFBM-Tpb-5 and b-PFBP-Tbp-5 (Example 8), respectively.

[0112] The synthetic route is shown in Scheme 4.

[0113]

[0114] Scheme 4. Synthetic route for poly(fluorene-co-biphenyl N,N-dimethylpiperidinium) copolymer ionomers containing 1,3,5-triphenylbenzene branches

[0115] [Example 9] Preparation of anion exchange membrane from branched poly(arylpiperidinium) copolymer ionomers

[0116] The branched poly(arylpiperidinium) copolymer ionomer (1.7 g) prepared in Examples 1 to 8 was dissolved in dimethyl sulfoxide to form a polymer solution having a concentration of 4 wt%. The polymer solution was then filtered using a 0.45 μm PTFE filter, and the resulting transparent solution was cast on a 21 cm×24 cm glass plate. The cast solution was dried in an oven at 90° C. for 24 hours to gradually remove the solvent, and then the solvent was completely removed by heating in a vacuum oven at 140° C. for 12 hours to obtain a membrane (I- form, thickness 25±5μm).

[0117] The obtained - The membrane was immersed in 1 M NaOH aqueous solution for 24 h to convert the counter ions into OH - and washed several times with ultrapure water, and then dried to prepare an anion exchange membrane (the obtained anion exchange membrane sample was named in the same manner as the branched poly(arylpiperidinium) copolymer ionomer prepared in Example 1-8).

[0118] [Comparative Example 1] Preparation of anion exchange membrane from poly(arylpiperidinium) copolymer ionomers without branching

[0119] An anion exchange membrane containing no branched portion was prepared by forming the poly(diphenyl-co-terphenyl N,N-dimethylpiperidinium) copolymer ionomer obtained in the same manner as Example 1 into a membrane in the same manner as Example 9, except that triptycene was not used as a monomer, and was named PDTP.

[0120] [Comparative Example 2] Preparation of anion exchange membrane from poly(arylpiperidinium) copolymer ionomers without branching

[0121] An anion exchange membrane containing no branched portion was prepared by forming the poly(fluorene-co-biphenyl N,N-dimethylpiperidinium) copolymer ionomer obtained in the same manner as Example 3 into a membrane in the same manner as Example 9, except that triptycene was not used as a monomer, and was named PFBP.

[0122] [Test example]

[0123] Using the method described in Korean Patent Publication No. 10-2021-0071810 filed by the inventors of the present disclosure, test data such as mechanical properties, water absorption rate, swelling rate, and fuel cell performance of the anion exchange membranes prepared in the embodiments and comparative examples of the present disclosure were measured and evaluated.

[0124] Figure 1 The NMR ( 1 H NMR) spectrum, Figure 2 The NMR spectra of b-PDTM-Tbp-3.5 and b-PDTP-Tbp-3.5 prepared in Example 5 and b-PFBM-Tbp-3.5 and b-PFBP-Tbp-3.5 prepared in Example 7 are shown ( 1 H NMR) spectrum. The characteristic peak of triptycene was observed at 5.49 ppm, and the characteristic peak of 1,3,5-triphenylbenzene was observed at 7.8 ppm, confirming the synthesis of the branched poly(arylpiperidinium) copolymer.

[0125] Figure 3 The anion exchange membrane (I - Mechanical properties of anion exchange membranes prepared in the following forms (prepared from the copolymer ionomers obtained in Examples 1-8) and Comparative Examples 1 and 2.

[0126] Due to the structure including the branched portion according to the embodiment of the present disclosure and the increased molecular weight and entangled structure, the tensile strength and elongation are higher than those of the comparative example not including the branched portion, and the increased mechanical strength contributes to improved battery performance and durability.

[0127] Figure 4 The anion exchange membrane (OH - The swelling ratio and water absorption ratio of the anion exchange membranes prepared in the form of copolymer ionomers obtained in Examples 1-8) and Comparative Examples 1 and 2.

[0128] The branched copolymer ionomer membranes according to the present disclosure show lower swelling ratio and higher water absorption ratio than conventional copolymer ionomer membranes without branched moieties due to their high molecular weight, supramolecular chain-threading, chain reaction, π-π stacking interaction, high ion exchange capacity (IEC) and improved free volume.

[0129] Generally, when water absorption and ion conductivity are high, the swelling rate increases. Although the branched copolymer ionomer membrane according to the present disclosure exhibits high water absorption, since the branched portion can suppress the swelling rate, desired physical properties can be achieved.

[0130] In other words, the structure including the branched portion of the present disclosure can resolve the contradiction between ionic conductivity and swelling rate due to high water absorption rate and improved dimensional stability and mechanical strength of the anion exchange membrane.

[0131] Figure 5 The hydrogen permeability of the anion exchange membrane prepared in Example 9 (prepared from the copolymer ionomers obtained in Examples 1 to 8) and the anion exchange membrane prepared in Comparative Example 1 are shown.

[0132] Due to the increased free volume of the rigid branched structure according to the present disclosure, the hydrogen permeability of the ionomer used in the catalyst layer is improved. This improved hydrogen permeability can reduce the mass transfer resistance of the reactants during the electrochemical reaction and help form the three-phase interface of the catalyst layer.

[0133] Figure 6The fuel cell performance of the anion exchange membrane prepared in Example 9 with different anode and cathode binders b-PDTP-Trip-5 [Binder A / C b-PFBP-Trip-3.5 according to Example 3 and Binder A / C b-PFBP-Trip-5 according to Example 4] is shown, and Figure 7 The fuel cell performance of b-PDTP-Trip-3.5 and b-PDTP-Trip-5 is shown, where the anode and cathode binders of b-PFBP-Trip-5 according to Example 4 were applied to the anion exchange membrane prepared in Example 9. They showed 2.5 W cm at high relative humidity (RH), H2-O2@80 °C and 1.3 bar. -2 The excellent performance of the composite is similar to that of the original structure.

[0134] Figure 8 The fuel cell performance of the anion exchange membrane prepared in Example 9 with different anode and cathode binders b-PDTP-Trip-3.5 [Binder A / C b-PFBP-Trip-3.5 according to Example 3 and Binder A / C b-PFBP-Trip-5 according to Example 4] under low humidity conditions is shown, and Fig. 9 The fuel cell performance of b-PDTP-Trip-3.5 and b-PDTP-Trip-5 is shown, where the anode and cathode binders of b-PFBP-Trip-3.5 according to Example 3 were applied to the anion exchange membrane prepared in Example 9.

[0135] They showed 1.6 W cm at low relative humidity (RH), H2-O2@80 °C and 1.3 bar. -2 This indicates that due to the improved free volume, high ionic conductivity, high water absorption and improved three-phase interface of the branched ionomer-containing catalyst layer according to the present disclosure, excellent fuel cell performance is achieved even at low humidity and low gas flow rate.

[0136] Fig.10 The water electrolysis performance of b-PDTP-Trip-5 is shown, in which the anion exchange membrane prepared in Example 9 was used according to the content of the anode and cathode ionomers. The b-PDTP-Trip-5 anion exchange membrane achieved 16 Acm at 80 °C and 2.0 V. -2 This corresponds to the highest performance known to date.

[0137] from Fig.11 It can be seen that the anion exchange membrane prepared in Example 9 has a -2The long-term stability was shown at 40 °C and 60 °C for 110 hours, where b-PDTP-Trip-5 was used as the membrane (membrane thickness 50 μm).

Claims

1. A branched poly(arylpiperidinium) copolymer ionomer having a repeating unit represented by [Chemical Formula 1]: [Chemical formula 1] The aromatic monomer is selected from one or more compounds represented by the following structural formula: Furthermore, the branching agent is selected from any one of the compounds represented by the following structural formulas:

2. A method for preparing a branched poly(arylpiperidinium) copolymer ionomer comprising: (I) a step of dissolving the following substances as monomers in an organic solvent to form a solution: (a) one or more compounds selected from the group consisting of the following structural formulae, (b) one or more compounds selected from the group consisting of the following structural formulae, and (c) 1-methyl-4-piperidinone; (II) a step of slowly adding a strong acid catalyst to the solution, and then stirring and reacting the solution to obtain a viscous solution; (III) a step of obtaining a solid polymer by precipitating, washing and drying the viscous solution; (IV) a step of adding K2CO3 and an excess of methyl halide to a polymer solution and reacting them to form a quaternary piperidinium salt, wherein the polymer solution is obtained by dissolving the solid polymer in an organic solvent; and (V) The steps of precipitating, washing and drying the polymer solution.

3. The method for preparing a branched poly(arylpiperidinium) copolymer ionomer according to claim 2, wherein: The organic solvent in step (I) is one or more halogen-based solvents selected from the group consisting of dichloromethane, chloroform, dichloroethane, dibromoethane and tetrachloroethane.

4. The method for preparing a branched poly(arylpiperidinium) copolymer ionomer according to claim 2, wherein: The strong acid catalyst in step (II) is trifluoroacetic acid, trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoro-1-propanesulfonic acid, perfluoropropionic acid, heptafluorobutyric acid or a mixture thereof.

5. The method for preparing a branched poly(arylpiperidinium) copolymer ionomer according to claim 2, wherein: The organic solvent in step (IV) is N-methylpyrrolidone, dimethylacetamide, dimethyl sulfoxide or dimethylformamide. 6 . An anion exchange membrane comprising the branched poly(arylpiperidinium) copolymer ionomer according to claim 1 .

7. A method for preparing an anion exchange membrane, comprising: (i) a step of dissolving the branched poly(arylpiperidinium) copolymer ionomer according to claim 1 in an organic solvent to form a polymer solution; (ii) a step of obtaining a film by casting the polymer solution on a glass plate and drying; and (iii) a step of treating the obtained membrane with 1 M NaHCO 3 or 1 M NaOH, washing the obtained membrane with ultrapure water several times and drying.

8. The method for preparing an anion exchange membrane according to claim 7, wherein: The concentration of the polymer solution is 2-30 wt%.

9. The method for preparing an anion exchange membrane according to claim 7, wherein: The drying in step (ii) is performed by gradually removing the organic solvent in an oven at 80 to 90° C. for 24 hours, and then completely removing the organic solvent by heating in a vacuum oven at 120 to 150° C. for 12 hours. 10 . A binder for an alkaline fuel cell, comprising the branched poly(arylpiperidinium) copolymer ionomer according to claim 1 .

11. An alkaline fuel cell comprising the anion exchange membrane according to claim 6.

12. A water electrolysis device comprising the anion exchange membrane according to claim 6.

13. A carbon dioxide reduction device comprising the anion exchange membrane according to claim 6.

14. A vanadium redox flow battery comprising the anion exchange membrane according to claim 6.

15. A metal-air battery comprising the anion exchange membrane according to claim 6.

Citation Information

Patent Citations

  • Poly(arylpiperidinium) polymers, including those with stable cationic pendant groups, for use as anion exchange membranes and ionomers

    JP2020536165A

  • Poly(aryl piperidinium) polymers for use as hydroxide exchange membranes and ionomers

    KR1020180121961A

  • A novel polyfluorene-based ionomer, an anion exchange membrane and method for preparing the same

    KR1020210071810A

  • Poly(aryl piperidinium) polymers for use as hydroxide exchange membranes and ionomers

    US20190036143A1

Cited By

  • Porphyrin-based branched ionomer, preparation method thereof and application of porphyrin-based branched ionomer as binder

    CN121537617A

  • A branched ionomer based on porphyrin, its preparation method and use as a binder

    CN121537617B